The Roles of Anandamide, Fatty Acid Amide Hydrolase, and Leukemia Inhibitory Factor on the Endometrium during the Implantation Window - Cui, Na; Wang, Changyan; Zhao, Zhiming; Zhang, Jie; Xu, Yueming; Yang, Yang; Hao, Guimin (Frontiers in Endocrinology, 2017)
Background/Aims: We investigated the role of the endocannabinoid system (ECS) in the endometrium of unexplained infertility (UI) patients, and effect of anandamide (AEA) on leukemia inhibitory factor (LIF). Methods: Patients were divided into UI and control groups. Endometrium samples were collected at the midluteal phase. Levels of cannabinoid type 1 (CB1), fatty acid amide hydrolase (FAAH) and LIF were examined. LIF productions were measured after AEA, CB1 antagonist AM251 and CB2 antagonist AM630 stimulation. Results: Rates of available embryo, successful implantation and pregnancy, and the endometrial thickness of UI group were significantly lower than control, suggesting uterine receptivity was decreased in UI group. FAAH and LIF levels were significantly decreased, while endometrial CB1 was slightly increased in UI group. LIF production was promoted by low amount of AEA administration (1-10 uM), while the promotion was reduced by higher concentration of AEA (50 uM). LIF levels were decreased by AM251 or AM630, compared with AEA alone. Expressions of FAAH and LIF were closely associated with uterus receptivity and implantation rate of UI patients. Different concentrations of AEA could stimulate dynamic changes in LIF production. Conclusion: Our data indicated the important role of the ECS in human fertility, which may promote new strategies for successful implantation and treatments for reproductive diseases.